2018
DOI: 10.1016/j.fct.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Caramel color safety – An update

Abstract: Caramel color has been used in foods and beverages for over 150 years and is globally regulated as a color additive. The four distinct classes of caramel color (Plain Caramel, Sulfite Caramel, Ammonia Caramel, and Sulfite Ammonia Caramel) are well characterized and each have specifications that take into account processing variables including reactants that can give rise to low molecular weight constituents (e.g., 4-MeI and THI) that may have toxicological significance for evaluating safety. Extensive safety t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 74 publications
2
28
0
6
Order By: Relevance
“…C-IV dye production process is characterized by the presence of nitrogen and sulfur in their manufacture chemical reactions, and its production leads to the high molecular weight constituents (HMW) formation (responsible for color differentiation) and low molecular weight constituents (LMW) formation (responsible for unintentional substances such as 4-methylimidazole (4-MeI)) 5 . The effects of oxidative damage after C-IV administration here may be associated with 4-MEI, also classified as a human carcinogen and the most potent neurotoxic substance by the International Agency for Research on Cancer 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…C-IV dye production process is characterized by the presence of nitrogen and sulfur in their manufacture chemical reactions, and its production leads to the high molecular weight constituents (HMW) formation (responsible for color differentiation) and low molecular weight constituents (LMW) formation (responsible for unintentional substances such as 4-methylimidazole (4-MeI)) 5 . The effects of oxidative damage after C-IV administration here may be associated with 4-MEI, also classified as a human carcinogen and the most potent neurotoxic substance by the International Agency for Research on Cancer 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This additive is produced through sulphite-ammonia process; some acids and alkalis may also be added during its production 4 , as sulfuric or citric acid, phosphoric, acetic and / or carbonic acid; alkalines such as hydroxides or mixtures of sodium, potassium and / or calcium; and salts such as carbonate, hydrogen carbonate, sulfate and ammonium, phosphate sodium, potassium or calcium. Some ammonium compounds, such as carbonate and ammonium hydrogen carbonate may also be added 5 . In this process, an ammonia interaction leads to sugar reduction, and byproducts such as 4-methyl imidazole (4-MEI) generation, which might presents highly toxic effects, such as neurological and cancerous pathologies 6 which lead, for example, the State of California to classify ut as a “cancer-causing chemical” 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caramel colors are food color additives that are classified as Class I, II, III, or IV based on the reactants used during their manufacture and their suitability for use in certain foods. Among them, Class III and IV caramel colors are commonly used for coloring various foods and soft drinks, and are produced by heating rich carbohydrates in the presence of ammonium compounds or both ammonium and sulfite‐containing compounds, respectively . It has been reported that these manufacturing processes generate 4‐methylimidazole (4‐MEI), a nitrogen‐containing heterocyclic organic compound derived from imidazole .…”
Section: Introductionmentioning
confidence: 99%